Reactive and pre-planned agility in young tennis players - Germic, A. (Baltic Journal of Sport and Health Sciences, 2025)
Background: In tennis, movement efficiency can be described as agility, which is crucial for adapting to the fast-paced and unpredictable nature of the game and affects a player`s ability to position themselves effectively and react to their opponent`s shots. While most studies focus on pre-planned movements, fewer address the cognitive and reactive components that mirror real match scenarios, highlighting the need for a more comprehensive approach to assessing agility in tennis.